Resilience in the blood transfusion process: Everyday and long-term adaptations to 'normal' work. (December 2019) - Watt, Alison; Jun, Gyuchan Thomas; Waterson, Patrick
Highlights: Transfusion adaptations show differences between work-as-imagined and work-as-done. Adaptation triggers are mostly due to staff issues or poor information technology. Tasks and processes are often adapted instead of the underlying trigger problem. Most adaptations are forced workarounds, while a few are proactive improvements. Managers are often unaware of adaptations, so fail to learn from resilient practice. Abstract: Blood transfusion is considered one of the safer aspects of healthcare, however potentially avoidable patient-safety incidents led to 14 deaths in the United Kingdom in 2017. Improvement initiatives often focus on staff compliance with standard operating procedures. This fails to understand adaptations made in a complex, dynamic environment, so the aim of this study is to examine the extent and nature of adaptations at all stages of the vein to vein transfusion process. Thirty-seven employees described sixty-six adaptations in their transfusion practices, showing clear differences between what has been characterised as work-as-imagined (WAI) and work-as-done (WAD). An analysis of the adaptations using the Systems Engineering Initiative for Patient Safety 2.0 (SEIPS 2.0) shows that triggers for adaptations were mostly staff-related or driven by poor information technology systems, but the resultant adaptations were usually amendments to tasks and processes. The majority of adaptations (83%) were forced – ideal solutions are not possible, so workarounds and coping strategies are required, but some (17%) were proactive – the surrounding system is adequate, but performance is improved by adapting. Managers or colleagues were largely unaware of adaptations made (79%) and, as a result, opportunities may be missed to identify and learn from resilient practices. The Concepts for Applying Resilience Engineering (CARE) model was further articulated in order to shed extra light on triggers and mechanisms. We make a number of suggestions regarding how we can better learn from adaptations and how these could be used to improve the safety of the blood transfusion process.